TANTANGAN DAN PELUANG PANDEMI COVID19 PADA TAMAN SAFARI PRIGEN BESERTA PENGELOLAANNYA - irenecn; Erna Andajani; Siti Rahayu (Jurnal Bisnis Terapan, 2022)
The COVID-19 pandemic has become the center of attention in all countries, including Indonesia. The unprecedented pandemic has made the tourism sector sluggish. Even though the tourism sector is an important sector for the Indonesian state, such as its large contribution to Gross Domestic Product (GDP), foreign exchange, the creation of new jobs, and many more. This unprecedented phenomenon has become the main objective of the research, namely to explore the challenges and opportunities during COVID19 on tourist attractions, especially at the Taman Safari Prigen, and impacts both positive and negative, which are closely related to tourist visits, and their management, giving rise to new prepositions. This study uses a qualitative method with a phenomenological approach. The paradigm used is interpretivism. The data of this research was obtained from primary data with a semi-structured interview method, which was carried out with internal and external parties at Taman Safari Prigen. The results of this study highlight the various challenges and opportunities faced by Taman Safari Prigen during the total closure of tourist attractions and reopening due to government regulations. Other challenges and opportunities, such as economic impacts, changes in marketing, changes in visiting patterns, adaptive action steps taken for animals, human resources and tourists, and so on. There are also multiple impacts found from every management decision taken which will be reviewed in this study.